Mind games : a novel [compact disc, unabridged] - Roberts, Nora (Macmillan Audio, 2024)
As they do each June, the Foxes have driven the winding roads of Appalachia to drop off their children for a two-week stay at their grandmother's. Here, twelve-year-old Thea can run free and breathe in the smells of pine and fresh bread and Grammie's handmade candles. But as her parents head back to suburban Virginia, they have no idea they're about to cross paths with a ticking time bomb. Back in Kentucky, Thea and her grandmother Lucy both awaken from the same nightmare. And though the two have never discussed the special kind of sight they share, they know as soon as their tearful eyes meet that something terrible has happened. The kids will be staying with Grammie now in Redbud Hollow, and thanks to Thea's vision, their parents' killer will spend his life in supermax. Over time, Thea will make friends, build a career, find love. But that ability to see into minds and souls still lurks within her, and though Grammie calls it a gift, it feels more like a curse-because the inmate who shattered her childhood has the same ability. Thea can hear his twisted thoughts and witness his evil acts from miles away. He knows it, and hungers for vengeance. A long, silent battle will be waged between them--and eventually bring them face to face, and head to head.